Komparasi Kekuatan Struktur Gedung Menara Suara Merdeka Semarang berdasarkan RSNI3 03-1726-201x (Gempa 2010) dan SNI 03-1726-2002 (Gempa 2002) - Riezky Ibnu Prasetyo; Rizky Novianto Wibowo; Windu Partono; Himawan Indarto (Jurnal Karya Teknik Sipil, 2013)
Menara Suara Merdeka Building was built by Suara Merdeka Group through its subsidiary PT. Merdeka Sandi Surya which has 17 floors and worth of 150 billion rupiahs. Menara Suara Merdeka (MSM) was built in Jalan Pandanaran no. 30 Semarang consists of two parts, the main (main building) and the parking (parking building) are quite spacious with the concept of green building. The building occupies an area of 3100 m2 with a capacity of 250 units of parking for cars and 350 motorcycles, including the parking area in the basement and semi-basement. Menara Suara Merdeka Building design based on the “SNI gempa 2002” (SNI 03-1726-2002). With the revision of “SNI gempa 2002” to “SNI gempa 2010” (RSNI3 03-1726-201x), the structure of the building was evaluated using the software SAP2000 v.10 by modeling the structure using standard seismic load of 2010 (RSNI3 03-1726-201x) and compare it with the 2002 earthquake loads (SNI 03-1726-2002). The results for spectrum response acceleration of the 2010 earthquake is 1.23 times greater than the 2002 earthquake, is enlarged due to Earthquake of 2010 and 2002 for Shear Story of 54.325%, 56.354% of Displacement and Story Drift of 56.342%. Based on SNI earthquake 2010 (RSNI3 03-1726-201x),the structure system of building is include to sway special (SRPMK). By using SRPMK, it was found that the beam and column reinforcement in accordance with the project design.